Scatter of dynamic response and damage of an arch dam subjected to artificial earthquake accelerograms. Issue 87 (August 2016) - Wang, Jin-Ting; Jin, Ai-Yun; Du, Xiu-Li; Wu, Ming-Xin
Abstract: In current engineering practice, artificial earthquake accelerograms are widely used in the seismic design of new dams. This study aims to investigate the seismic response and damage sensitivity of arch dams to artificial ground motions. A total of 32 accelerograms are artificially synthesized based on the design acceleration response spectrum. The nonlinear dynamic response of the Dagangshan Dam, an arch dam in Southwest China, to these artificial accelerograms is investigated. Dynamic response, including displacement and joint opening, and damage distribution are statistically analyzed. Results show that the seismic response and damage to a dam may significantly scatter for various accelerograms, even if the artificial accelerograms have the same response spectra, peak ground accelerations, velocities, and displacements. Graphical abstract: Statistics of the maximum joint opening for 32 artificial accelerograms. Highlights: We consider 32 artificial accelerograms with the same PGA, PGV, PGD, and design ARS. The seismic damage to a dam may significantly differ for various accelerograms. Some accelerograms may double the maximum displacement. The joint opening scatter more remarkable than the displacement.